2007
DOI: 10.4049/jimmunol.179.11.7916
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIa Genotype Predicts Progression of HIV Infection

Abstract: Polymorphisms in FcγR genes are associated with susceptibility to or severity of a number of autoimmune and infectious diseases. We found that HIV-infected men in the Multicenter AIDS Cohort Study with the FcγRIIa RR genotype progressed to a CD4+ cell count of <200/mm3 at a faster rate than individuals with the RH or HH genotypes (relative hazard = 1.6; p = 0.0001). However, progression to AIDS (using the broad definition of either a CD4+ cell count <200/mm3 or development of an AIDS-defining ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 70 publications
6
129
1
3
Order By: Relevance
“…Two groups separately demonstrated that HIV-infected subjects carrying a CD16 polymorphism, which increases the IgG binding of the receptor and enhances the NK cell ADCC potential (50), exhibit faster disease progression (51,52). It should be noted that an additional study by Forthal et al (53) did not observe an effect of CD16 polymorphisms on HIV disease progression. However, studies revealing a potential role for CD16 polymorphisms in HIV disease progression, in combination with the current study and other studies showing alterations in NK cell phenotype and functional potential as a result of activation through CD16 (26,29), suggest that a critical reassessment of the role of ADCC in chronic HIV infection is essential.…”
Section: Discussionmentioning
confidence: 82%
“…Two groups separately demonstrated that HIV-infected subjects carrying a CD16 polymorphism, which increases the IgG binding of the receptor and enhances the NK cell ADCC potential (50), exhibit faster disease progression (51,52). It should be noted that an additional study by Forthal et al (53) did not observe an effect of CD16 polymorphisms on HIV disease progression. However, studies revealing a potential role for CD16 polymorphisms in HIV disease progression, in combination with the current study and other studies showing alterations in NK cell phenotype and functional potential as a result of activation through CD16 (26,29), suggest that a critical reassessment of the role of ADCC in chronic HIV infection is essential.…”
Section: Discussionmentioning
confidence: 82%
“…Aberrant expression or the presence of certain allelic variations of FcγRs is associated with altered functionality that in turn is associated with susceptibility to, or increased severity of, certain autoimmune and infectious diseases and to outcomes of monoclonal Ab cancer treatments (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Besides IgG Abs, IgA Abs also play an important role in humoral immunity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, less is known about the role of Fc-mediated effector function in the control of HIV-1, although four lines of evidence signal its importance. First, studies in HIV-1-infected people (8)(9)(10)(11)(12)(13)(14) and in macaques infected with simian immunodeficiency virus (15,16) consistently show an inverse correlation between Fc-mediated effector functions, including antibody-dependent cell-mediated cytotoxicity (ADCC) (8,9) or antibody-dependent cell-mediated viral inhibition (ADCVI), and viral loads or decreased disease progression (17). Second, vaccine-elicited protection both in nonhuman primates (18)(19)(20)(21) and in a subset of human subjects in the Vax-004 trial (22) correlates with Fc-mediated effector function often observed in the absence of detectable neutralizing antibodies (18)(19)(20)(21).…”
mentioning
confidence: 99%